Effect of temperature, carbon fibers, and silica fume on the mechanical properties of lightweight concretes - Tanyildizi, Harun (Elsevier, 2008)
The effect of temperature, and carbon fiber and silica fume contents on the mechanical properties (compressive and flexural strength) of lightweight concretes was investigated. Samples containing silica fume (mass fractions of 0 and 10%) and carbon Fibers (mass fractions of 0, 0.5, 1, and 2%) were prepared. The compressive and flexural strengths of the samples were determined after they had been exposed to high temperatures (400, 600, and 800 degrees C). The Taguchi method was used to determine the optimum conditions and to reduce the number of experiments. The significance of the three factors affecting the mechanical properties of lightweight concretes was determined using the Anova analysis and the F-test. Results showed that the most important factor for mechanical properties was temperature, followed by carbon fiber and silica fume contents. The optimum parameters for compressive strength were different from those for flexural strength.
Keywords: Lightweight concrete; Carbon fibers; Mechanical properties; Variance (Anova) analysis; Taguchi method